A drill-hole calibrated geophysical characterisation of the 23 Ma Foulden Maar stratigraphic sequence, Otago, New Zealand. Issue 4 (2nd October 2017) - Jones, Daniel A.; Wilson, Gary S.; Gorman, Andrew R.; Fox, Bethany R. S.; Lee, Daphne E.; Kaulfuss, Uwe
ABSTRACT: The Foulden Maar is a terrestrial monogenetic volcanic crater found within the latest Oligocene–Late Miocene Waipiata Volcanic Field on the South Island of New Zealand. A geophysical characterisation of the Foulden Maar has been calibrated by acquiring a continuous 184 m drill core through the feature, which includes well preserved crater-lake sediments. Interpretations of gravity profiles, airborne and land-based magnetic data, and seismic reflection surveys reveal the geometry, density distribution and stratigraphy of the volcanic feature that formed on and in the schist basement of Central Otago. Six significant horizons are identified within a synthetic seismogram that ties core logs to the geophysical data. The investigation confirms a classic maar and diatreme structure consisting of a 1–1.5 km wide, c. 300 m deep crater overlying a thin vertical diatreme structure.